Vaccines: Are they Worth a Shot? - Grignolio, Andrea (Springer International Publishing, 2018)
The dangerous decline in vaccinations in many developed countries is at the heart of a lively debate that confirms how important the subject is today. Vaccinations are among mankind's most important scientific discoveries, yet they continue to be viewed with suspicion by part of the public - the victims of disinformation campaigns, instrumentalization and unfounded fears. There is, however, also an evolutionary explanation for these irrational beliefs, and countering the growing social opposition will be extremely difficult without grasping it. This book, which sheds new light on the safety and importance of vaccinations, is intended both for parents and those readers who want to understand the role of vaccinations in contemporary society, where the ease of access to knowledge is both a great opportunity and a great responsibility. The chapters follow a historical progression and conclude with a discussion of the most recent cognitive theories on how to overcome this opposition to vaccinations.